The Social Cost of Carbon: Trends, Outliers and Catastrophes - Richard S. J. Tol (Kiel Institute for the World Economy (IfW), 2007)
211 estimates of the social cost of carbon are included in a meta-analysis. The results confirm that a lower discount rate implies a higher estimate; and that higher estimates are found in the gray literature. It is also found that there is a downward trend in the economic impact estimates of the climate; that the Stern Review?s estimates of the social cost of carbon is an outlier; and that the right tail of the distribution is fat. There is a fair chance that the annual climate liability exceeds the annual income of many people.
Keywords: Q54; 330; Climate change; social cost of carbon